The role of rhythmic factors in the perception of time - Oxtoby, Richard Markham (Department of Psychology, 2016)
In the past, research into the perception of time and the perception of pattern have proceeded independently. In the present study, the effect of the patterning of stimuli on the perception of time is investigated, and a theory of time perception elaborated. An experiment designed to investigate some of the factors postulated in this theory is described. It is suggested that really significant results can only be expected from a close analysis of the performance of individuals. Such an analysis of the data from this experiment provides definite evidence for the existence of some of the processes postulated in the theory.